Traditional wisdom meets artificial intelligence - Haggith, M.; Colfer, C.J.P. (1999)
This short article describes an unlikely, but fruitful, collaboration between an anthropologist and an Artificial Intelligence researcher, the purpose of which was to build a model of how indigenous Dayak people in Kalimantan decide on their activities in the forest. The approach and the results are described. The simple model developed used relations and logic to capture some of the Dayak decision-making processes. The model used Prolog programming language. In building the model, an exploration was made of how opportunities for giving and receiving favours might form an alternative to conventional methods of modelling choices between actions, such as economic optimization.